Effects of Welfare Reform on Women's Voting Participation - Dhaval M. Dave; Hope Corman; Nancy E. Reichman (Institute for the Study of Labor (IZA), 2016)
Voting is an important form of civic participation in democratic societies but a fundamental right that many citizens do not exercise. This study investigates the effects of welfare reform in the U.S. in the 1990s on voting of low income women. Using the November Current Population Surveys with the added Voting and Registration Supplement for the years 1990 through 2004 and exploiting changes in welfare policy across states and over time, we estimate the causal effects of welfare reform on women's voting registration and voting participation during the period during which welfare reform unfolded. We find robust evidence that welfare reform increased the likelihood of voting by about 4 percentage points, which translates to about a 10% increase relative to the baseline mean. The effects were largely confined to Presidential elections, were stronger in Democratic than Republican states, were stronger in states with stronger work incentive policies, and appeared to operate through employment, education, and income.
Keywords: H0; I2; J2; J3; 330; employment; voting; welfare reform; income; civic participation; education; difference-in-differences